Assessment of H3K27me3 immunohistochemistry and combination of NF1 and p16 deletions by fluorescence in situ hybridization in the differential diagnosis of malignant peripheral nerve sheath tumor and its histological mimics - Shintaro Sugita; Tomoyuki Aoyama; Makoto Emori; Tomomi Kido; Tomoko Takenami; Kodai Sakuraba; Kotomi Terai; Taro Sugawara; Mitsuhiro Tsujiwaki; Tadashi Hasegawa (BMC, 2021)
Abstract Background A definitive diagnosis of malignant peripheral nerve sheath tumor (MPNST) is challenging, especially in cases without neurofibromatosis 1 (NF1), because MPNST lacks specific markers on immunohistochemistry (IHC). Methods We performed IHC for histone 3 trimethylated on lysine 27 (H3K27me3) and evaluated the percentage of cells with H3K27me3 loss using measured values at 10% intervals, categorized as complete loss (100% of tumor cells lost staining), partial loss (10% to 90% of tumor cells lost staining), and intact (no tumor cells lost staining). We conducted fluorescence in situ hybridization (FISH) for NF1 and p16 deletions comparing 55 MPNSTs and 35 non-MPNSTs, consisting of 9 synovial sarcomas (SSs), 8 leiomyosarcomas (LMSs), 10 myxofibrosarcomas (MFSs), and 8 undifferentiated pleomorphic sarcomas (UPSs). We assessed the percentage of cells with homozygous and heterozygous deletions and defined "deletion" if the percentage of either the NF1 or p16 deletion signals was greater than 50% of tumor cells. Results Among the 55 MPNSTs, 23 (42%) showed complete H3K27me3 loss and 32 (58%) exhibited partial loss or intact. One each of the 9 SSs (11%), 8 LMSs (12%), and 8 UPSs (12%) showed complete H3K27me3 loss and many non-MPNSTs exhibited intact or partial H3K27me3 loss. Among the 55 MPNSTs, 33 (60%) and 44 (80%) showed NF1 or p16 deletion, respectively. Co-deletion of NF1 and p16 was observed in 29 (53%) MPNSTs. Among the 23 MPNTSs showing H3K27me3 complete loss, 18 (78%) and 20 (87%) exhibited NF1 or p16 deletion, respectively. Among the 32 MPNSTs with H3K27me3 partial loss or intact, 15 (47%) and 24 (75%) exhibited NF1 or p16 deletion, respectively. The frequency of NF1 and/or p16 deletion tended to be lower in non-MPNSTs than in MPNSTs. Approximately 90% of MPNSTs included cases with H3K27me3 complete loss and cases showing H3K27me3 partial loss or intact with NF1 and/or p16 deletion. Approximately 50% of MPNSTs showed co-deletion of NF1 and p16 regardless of H3K27me3 loss. Conclusions FISH for NF1 and p16 deletions, frequently observed in high-grade MPNSTs, might be a useful ancillary diagnostic tool for differentiating MPNST from other mimicking spindle cell and pleomorphic sarcomas.